Evaluation of the financial challenges faced by contract farmers in achieving transformation in the agricultural sector in South Africa - Skepe, Siphelo (Graduate School of Business (GSB), 2021)
Access to finance is an essential factor in the agricultural value chain and enables participants to purchase essential inputs and infrastructure (e.g. machinery and land) necessary for the production process, grading, processing, packaging and distribution of their produce. Finance is also required where there are specific regulatory requirements (such as licencing and certification) to which a participant must adhere, and these may differ from commodity to commodity. With this in mind, it is clear that any farming enterprise that wishes to enter and participate in the agricultural sector will need access to finance to compete effectively. The study examines the financial needs and challenges faced by contract farmers in achieving transformation in the agricultural sector in South Africa. In line with the number of interviews conducted in other qualitative studies, a sample of eight contract farmers from Gauteng, North West, Mpumalanga, KwaZulu-Natal and Free State provinces of South Africa were chosen for the interviews. The study finds that purchase of land, farming infrastructure, farming equipment, working capital for agricultural inputs, and funds for environmental impact assessments are the prevalent financial needs of the sampled contract farmers. Most importantly, the study further documents evidence that business and financial understanding, lack of capital, insufficient collateral, the lending criteria and policies of financial institutions and rigid and non-inclusive products are the major challenges faced by black contract farmers in raising funds to meet their financial needs and their contractual obligations to their sponsors. The study recommends ways in which the farmers believe they could be part of the solution in financially assisting new and emerging farmers and creating a transformed agricultural sector in the country. Farmers believe that this requires a concerted effort by all the stakeholders to close the existing gaps in the current financial mechanisms used to finance farmers in South Africa. It is important that the critical stakeholders (government, development financial institutions and other financial institutions, farmers and their organisations, sponsors and agroprocessors) work closely together so that more can be achieved in the least possible time period. The role of each of the above stakeholders is discussed in the recommendations chapter.